2019
DOI: 10.3390/w11102040
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Operation of Cascade Hydropower Reservoirs Using TOPSIS and Gravitational Search Algorithm with Opposition Learning and Mutation

Abstract: In this research, a novel enhanced gravitational search algorithm (EGSA) is proposed to resolve the multi-objective optimization model, considering the power generation of a hydropower enterprise and the peak operation requirement of a power system. In the proposed method, the standard gravity search algorithm (GSA) was chosen as the fundamental execution framework; the opposition learning strategy was adopted to increase the convergence speed of the swarm; the mutation search strategy was chosen to enhance th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…For most evolutionary methods, all the individuals may fail to jump out of local optima and it is necessary to find some methods to enlarge the hunting range of the swarm [59]- [61].…”
Section: B the Proposed Igwo Methods 1) Quasi-oppositional Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…For most evolutionary methods, all the individuals may fail to jump out of local optima and it is necessary to find some methods to enlarge the hunting range of the swarm [59]- [61].…”
Section: B the Proposed Igwo Methods 1) Quasi-oppositional Learningmentioning
confidence: 99%
“…In recent years, the opposition-based learning comparing the performances of the current solution and its opposite solution at the same time is often used to improve the performance of evolutionary method [59]- [61]. For any one solution, Equation ( 13) can be used to obtain the quasi-opposite position.…”
Section: B the Proposed Igwo Methods 1) Quasi-oppositional Learningmentioning
confidence: 99%
“…Due to climate change, the importance of reservoirs is likely to increase, not only for water storage purpose but also for maximizing water use benefits and mitigating climate extremes. Four papers [9][10][11][12] employ advanced optimization methods to derive reservoir operating rules for multi-reservoir systems and/or optimize multi-objective reservoir operation. In [9], the authors conduct a multi-target single dispatching study on ecology and power generation in the lower Yellow River to solve the single-objective and the multi-objective optimal schema using the genetic algorithm (GA) and an improved non-dominated genetic algorithm (NSGA-II).…”
Section: Summary Of the Papers In The Special Issuementioning
confidence: 99%
“…Multidisciplinary research and advanced methodologies in hydrological forecasts, especially in extreme floods and droughts, are widely implemented for water planning and management, which ultimately lead to improved optimum water resources management and effective control under a changing environment. Among them, artificial intelligence (AI) techniques are efficient tools for extracting the key information from complex highly dimensional input-output patterns and are widely used to tackle various hydrological problems such as flood forecasts discussed in this Special Issue [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Over the last decades, many studies have demonstrated that artificial intelligence (AI) techniques, such as machine learning (ML) methods, can produce flood forecasts in a few hours [15][16][17][18][19] while extending to seasonal forecasts many months in advance for larger river basins [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In the multiobjective optimization framework, many methods have been developed for the selection of an optimal solution from a given set of Pareto non-dominated ones [28,29]. In this work, the technique for order of preference by similarity to ideal solution TOPSIS is used to make decision about the optimal solution for problem (5).…”
Section: Proposed Planning Proceduresmentioning
confidence: 99%